Developing a Diamond Framework Model Based on "Integration" of Project Success Measures for Construction Project Management in Yemen - Kuhail, Muaadh Yahya Al-; Al-Dafiry, Hamoud Ahmed; Barakat, Tarek Abdullah; Al-Ansi, Abdulwahad (University of Putra Malaysia Press, 2021)
The most prominent obstacle facing the construction industry in Yemen is mismanagement. Developing appropriate tools, approaches, and standards for managing construction projects will contribute effectively to the development and prosperity of the Yemeni construction industry. This study aims to provide the tools, approaches and standards for project management based on the opinions of the Yemeni advisory bodies. It presents an Integrated Cost, Quality, Time, and Scope (ICQTS) diamond framework model by developing the traditional triangle model in project management providing a practical contribution to researchers and companies working in the construction industry. The study uses a descriptive and analytical approach through a comprehensive literature review followed by a field study using a designed questionnaire distributed to the relevant Yemeni advisory bodies. The study concluded with the development of the traditional triangle model resulting in the introduction of the diamond framework model in the management of construction projects. Integration management was found to have a strong impact on project success presenting the framework model as an easy and flexible tool that unifies and integrates the processes and roles in the project and directing it towards achieving project stakeholder objectives. The literature largely neglects the impact of integration management in the various models and is mostly overlooked. Inclusion of integration management in the presented model will highlight measures of project success stressing the need to integrate and manage them together. Future studies may research the differences in the opinions of construction companies.